A novel acrosomal protein, IQCF1, involved in sperm capacitation and the acrosome reaction. (7th November 2014) - Fang, P.; Xu, W.; Li, D.; Zhao, X.; Dai, J.; Wang, Z.; Yan, X.; Qin, M.; Zhang, Y.; Xu, C.; Wang, L.; Qiao, Z.
Summary: On the basis of the unknown tags in the mature human sperm serial analysis of gene expression library constructed by our laboratory, some transcripts were cloned, including Iqcf1 ( IQ motif containing F1 ). To investigate the function of sperm‐retained Iqcf1 in spermatogenesis and fertilization of mice, we investigated the spatial and temporal expression of IQCF1. By using the (transcription activator‐like effector nuclease) strategy, Iqcf1 ‐knockout mice were produced, and the phenotypes of the Iqcf1 −/− mice were analyzed. The results showed that IQCF1 was localized in the acrosome of spermatozoa and spermatids; the expression of IQCF1 in testes was associated with spermatogenic capacity. The Iqcf1 −/− mice were significantly less fertile than the wild‐type mice ( p  = 0.0057) because of reduced sperm motility ( p  = 0.0094) and the acrosome reaction (AR) ( p  = 0.0093). In spermatozoa, IQCF1 interacted with calmodulin (CaM) and possibly participated in the tyrosine phosphorylation of sperm proteins during capacitation. In conclusion, a newly identified acrosomal protein, IQCF1, is closely related to sperm capacitation and AR; in particular, it is involved in tyrosine phosphorylation of sperm proteins through interaction with CaM. Research into the function of IQCF1 during fertilization could facilitate the investigation of the molecular mechanism of capacitation, which is unclear.